Diseño de un sistema inalámbrico de estimulación eléctrica funcional adaptativo - Higuera González, Rogelio Manuel; Bello Cruz, Lilian Angélica; Ortiz Flores, Victor Hugo (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
In recent years, Functional Electrical Stimulation (FES) became a promising rehabilitation treatment for Spinal Cord Injuries (SCI). Different topologies for FES systems have been implemented to rehabilitate specific muscles, but this limits their adaptability for the stimulation of any other one. On the other hand, many of these designs are limited in portability because they do not use wireless technology. In this paper, we propose the design of an FES system that generates monophasic and biphasic current pulses in an amplitude range of 0 to 26 mA. In addition, the output stage of the FES system we propose, includes the use of a differential current source, whose amplitude can be manipulated by means of two digital potentiometers. Waveform, amplitude, frequency and pulse width can be manipulated directly from the Graphical User Interface (GUI) of the FES system. Moreover, a wireless interface was implemented between the computer and the system to give greater portability to the user and more movility to the patient. All these features make our design adaptable for different rehabilitation treatments.